Diagnosis of alveolodental ankylosis in unerupted canines: one of the answers to why the canine does not come - Alberto Consolaro; Omar Hadaya; Mauricio de Almeida Cardoso (Dental Press Editora, 2021)
ABSTRACT Introduction: Teeth frequently fail to erupt and situations arise that prevent the canines from reaching the occlusal plane. Objective: Discourse about the three situations in which the canine does not reach the occlusal plane, and remains unerupted; and at the same time, point how to make a safe diagnosis of alveolodental ankylosis - one of the three causes -, based on tomography. Conclusions: Ankylosis occurs in impacted teeth by atrophy of the periodontal ligament, including the epithelial rests of Malassez. The tomographic signs of alveolodental ankylosis in unerupted canines are the interruption of hypodense periodontal space, discontinuity of the lamina dura and its continuity with the root surface, which gradually loses its regular shape.